The Effect of the STEM Approach on Learning Outcomes of Elementary School Students - Muhammad Nurwahidin; Lungit Wicaksono; Deviyanti Pangestu; Maman Surahman (BIRCU, 2023)
The problem in this study is the low science learning outcomes of fifth grade students at state elementary school 2 wonodadi. This study aims to determine the effect of the Science, Technology, Engineering, and Mathematics (STEM) approach on students' natural science learning outcomes. The type of research used is quantitative research with quasi-experimental methods and research designs in the form of non-equivalent control group designs. Determination of the research sample using purposive sampling, with a research sample consisting of 57 students. The results of the hypothesis test showed that there was a significant difference in learning outcomes between the group that applied the STEM approach and the group that applied the scientific approach to science learning outcomes. From the results of the hypothesis testing, it can be concluded that there is an influence of the Science, Technology, Engineering and Mathematics (STEM) approach to the science learning outcomes of students in class fifth grade elementary school, and there are positive and significant differences in the STEM approach in the experimental class compared to the scientific approach in the control class towards science learning outcomes of class fifth grade students at state elementary school 2 wonodadi